REINTERPRETASI SANGKAN PARANING DUMADI SEBAGAI KERANGKA INTERDISIPLINER KEBERLANJUTAN DAN IDENTITAS BUDAYA JAWA - Setiawan, Agus; Senoprabowo, Abi; Akrom, Ahmad; Muqoddas, Ali; Bastian, Henry (CITRAKARA, 2025)
Sangkan Paraning Dumadi is a fundamental Javanese philosophical concept that emphasizes the ontological interconnectedness between humans, nature, and the divine. In facing global challenges such as climate change, ecological degradation, and cultural identity crises, this philosophy has renewed relevance as an ethical and epistemic foundation for sustainable development. This study aims to reinterpret Sangkan Paraning Dumadi through an interdisciplinary lens and examine its implications for environmental sustainability, social resilience, and cultural identity reinforcement. This research applies a qualitative method through literature review. The findings indicate contributions to ecological ethics, community resilience, and cultural revitalization within global dynamics.